The Phenomenon Of The Instagram Stories Feature As A Medium For Student Self-Existence - Rindiani Rindiani; Anis Endang; Yanto Yanto (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
This study aims to describe the phenomenon of using the instagram stories feature as a medium to express student self-existence. In the digital and media era, Instagram stories are one of the platforms used by Dehasen University's 2020 Communication Science students for various aspects of their lives. The results showed that students actively use the instagram stories feature to describe their identity and self-existence. Their stories postings include a variety of content, such as pictures, videos, short stories, quotes, and daily activities. Through content analysis, this study identifies patterns in the way students construct their self-existence on this social media. This research also discusses the impact of using Instagram Stories on students' social interactions and self-perception. This research uses Qualitative research methods. The subjects of this study consisted of 4 informants from the Dehasen University Class of 2020 Communication Science Study Program. Data collection techniques were carried out by observation, interviews, and documentation. The results show that this platform plays an important role in building social relationships, increasing self-confidence, and providing opportunities to express their interests, values, and aspirations.